MEDIA IKLAN PROFIL SMA-IT ALIA TANGERANG BERBASIS ANIMASI 3D - Dewi Immaniar; Triyono Triyono; Richi Setiawan (CCIT Journal, 2014)
The development of multimedia technology , especially information technology today has grown more rapidly thereby making human life had now become so easy and fun . One area that can be combined with the development of the field of multimedia can be found in the advertising world , especially in education . Problems often occur advertising to promote the schools still less varied and less Mltimedia highlight developments that have been developed . The new breakthrough is needed , and in this case can be taken is a video profile which is often used as a medium for the introduction and promotion of schools in Indonesia . There are various types of advertising and video profiles are often produced , ranging from entirely ditokohkan and played by real human or using a 3D animation of characters that made ??such that it has the properties and behavior of human beings . By using Google Sketch up and 3D Max are arranged to create a frame by frame animation in the form of promotional advertising . Media Advertising Profile IT ALIA TANGERANG SMA – Based 3D Animation feature a wide range of excellence and achievement in high school there – IT ALIA . 3D advertising will reveal the main developments in the information technology IT ALIA high school that was already growing . This animation -based advertising media can contribute to increase the target of new students with a unique breakthrough advertising with 3D animation .